RANCANG BANGUN SISTEM PELAYANAN PELANGGAN RESTORAN ABC BERBASIS WEB - Supriyanto Karya (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
The development of information technology in the world is so fast compared to last decade. The effects on our daily lives are so big because people keeps demanding for better technology. Better technology means that various parts of the industry can be improved and reducing cost and time required for the business process. Service industry is one of the industries which improved thanks to the technology development. Faster service means more people can be taken care of which results in growing profit. This research aim is to implement technology in service industry to surpass the limit of human and take care of any weakness in various parts of the industry.Â Key words : Web, Restaurant, CodeIgnite